2011
DOI: 10.1016/j.cell.2011.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Cross-Activation of GRPR by MOR1D Uncouples Itch and Analgesia Induced by Opioids

Abstract: SUMMARY Why do opiates make human beings itch ? Spinal opioid-induced itch, a prevalent side effect of pain management, has been considered to occur as a result of pain inhibition. We report that morphine-induced scratching (MIS) is abolished in mice lacking either gastrin-releasing peptide receptor (GRPR) or the μ opioid receptor (MOR). Using exon-specific knockdown, we identified the MOR1D isoform as essential for MIS, whereas MOR1 is important for morphine-induced analgesia (MIA) with no cross activity pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
259
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(273 citation statements)
references
References 68 publications
6
259
2
6
Order By: Relevance
“…A recent study demonstrated that GRPR can heteromerize with an isoform of the μ-opioid receptor MOR1D (44). This interaction explains the usual itch that accompanies morphine treatments, which could now be inhibited by preventing the interaction between the two GPCRs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that GRPR can heteromerize with an isoform of the μ-opioid receptor MOR1D (44). This interaction explains the usual itch that accompanies morphine treatments, which could now be inhibited by preventing the interaction between the two GPCRs.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of an itch-specific pathway was supported by the identification of histamine-selective C fibers in human skin (9), and by the report that gastrin-releasing peptide (GRP) is an itch-selective transmitter of DRG neurons (10) that activates the GRP receptor (GRPR) on spinal neurons, which transmit itch but not pain (11). A heterodimer of the GRPR and a μ-opioid receptor (MOR) variant, MOR1D, in spinal neurons may mediate opioid-induced itch (12). However, sensory nerves in the skin are selective but not specific for histamine, since they also respond to nociceptive stimuli such as capsaicin (13), an agonist of the transient receptor potential vanilloid 1 channel (TRPV1), and DRG nociceptors expressing TRPV1 are necessary for scratching behavior (14).…”
Section: Introductionmentioning
confidence: 90%
“…In the spinal cord, the opioid μ-receptor isoform MoR1d heterodimerizes with the bombesin BB 2 receptor, and the stimulation of MoR1d by morphine produces an effect similar to the stimulation of the BB 2 receptor. 102) Analgesia induced by intracisternal injection of morphine is antagonized by naloxonazine, an opioid μ 1 -receptor antagonist, but scratching induced by intracisternal morphine is not inhibited by naloxonazine.…”
Section: Itch-inhibitory Systemmentioning
confidence: 99%